Pengaruh Metode Diskusi Presentasi Terhadap Hasil Belajar Pendidikan Agama Islam Siswa Kelas X SMA - Idos Idos; Sulaiman Sulaiman (An-Nuha, 2022)
The study was conducted to determine the effect of the application of the discussion and presentation method on the learning outcomes of Islamic Religious Education and Budi Pekerti in class X students at SMA N 1 Kecamatan Gunuang Omeh. This research is a quantitative experiment with the type of One-Shot Case Study. A sample of 28 respondents was taken using the Saturated Sampling Technique. Data were taken using tests, questionnaires, and documentation. The discussion method of the X¹ variable, the X² presentation method, and the learning outcomes of the Y variable. The data were analyzed by prerequisite tests, namely, normality, homogeneity, linearity, multicollinearity, heteroscedasticity, and multiple linear regression tests, hypothesis testing with F test, T test, and R² test. Obtained F arithmetic 0.160<F table 4.20, and T arithmetic discussion method -0.339< T table 2.048, presentation method obtained T arithmetic -0.205<Ttable 2.048, simultaneous and partial conclusions discussion and presentation methods do not affect learning outcomes of Religious Education Islam and Morals of class X students at SMA N 1 Kecamatan Gunuang Omeh. The result of the R² test is 1.3%.